The roles of Islamic legislation: a scientific review (Damascus University Journal for legal sciences, 2025)
The research aims to provide a scientific reading of the roles of Islamic legislation, as stated in the book "Introduction to Islamic Sharia", which is one of the joint university courses between the College of Law and the College of Sharia. In order to achieve the goal of the research, it was divided into three demands. The first requirement is about the nature of the roles of Islamic legislation, and the second requirement is in comparing the purposes of studying the roles of Islamic legislation with the purposes of studying the history of other laws, and the last requirement is in reviewing the ideas on which the roles of Islamic legislation were based, including: non-independent ijtihad in the Prophet’s era, and hypothetical or discretionary jurisprudence in the third legislative role, The emergence of schools of jurisprudence in the third legislative period, the activity of the codification movement for jurisprudence in the fourth legislative period, and the phenomenon of sectarian fanaticism in the fifth legislative period. The research followed the descriptive approach with its various tools, and reached a number of results, the most important of which are: The so-called roles of legislation after the era of the message have no relationship to the history of Islamic legislation, and therefore it is sufficient to study the era of the message, considering that it is the era in which the structure of Islamic law was completed.
Keywords: Roles of Islamic legislation; Introduction to Islamic law; History of law